The Practical Challenges of Servitized Manufacture - Baines, Tim S.; Lightfoot, Howard (Cranfield University Press, 2009)
Servitization is now widely recognised as the process of creating value by adding services to products. Since this term was first coined in the late 1980s it has been studied by a range of authors who have specifically sought to understand the methods and mechanisms of service-led competitive strategies for manufacturers. This paper reports on the experiences of a large company as they have moved towards servitized manufacture. This has been based on an extensive series of interviews with key personnel. The results of the study and implications for research are all reported.
Organised by: Cranfield University
Keywords: Manufacturing; Service; Case-study